Control of N‐Heterocyclic Carbene Catalyzed Reactions of Enals: Asymmetric Synthesis of Oxindole‐γ‐Amino Acid Derivatives. Issue 1 (5th December 2017) - Chen, Xiang‐Yu; Xiong, Jia‐Wen; Liu, Qiang; Li, Sun; Sheng, He; von Essen, Carolina; Rissanen, Kari; Enders, Dieter
Abstract: A strategy to control the switch between a non‐cycloaddition reaction and a cycloaddition reaction of enals, using N‐heterocyclic carbene (NHC) catalyisis, has been developed. The new scalable protocol leads to γ‐amino‐acid esters bearing a tetrasubstituted stereocenter in good yields and high stereoselectivities by homo‐Mannich reactions of enals and isatin‐derived ketimines. By simply changing the N‐ketimine substituent to an ortho ‐hydroxy phenyl group, the corresponding spirocyclic oxindolo‐γ‐lactams are obtained. Abstract : Switcheroo : An NHC‐catalyzed homo‐Mannich reaction between enals and isatin‐derived ketimines opens a novel, efficient, and highly stereoselective entry to oxindole‐γ‐amino esters. A simple change of the N‐ketimine substituent allows a switch to the formation of the corresponding spirocyclic γ‐lactams. NHC=N‐heterocyclic carbene.